Pengaruh Pola Asuh Orang Tua Terhadap Pembentukan Karakter Kristiani Anak Usia Dini di Paud Gkpi Jemaat Khusus Hutagalung Tahun Ajaran 2022/2023 - Santi Murni Telaumbanua; Uranus Zamili; Adiani Hulu (Pusat Riset dan Inovasi Nasional, 2023)
Telaumbanua, Santi Murni. 2023. “The Influence of Parenting Pattrens on the Formation of Christian Character in Early Childhood in PAUD GKPI Hutagalung Special Congregation for the 2022/2023 Academic Year.” Thesis: Early Childhood Christian education Study Program, Tarutung State Christian Institute. The aim of this research is to determine the influence of parenting patterns on the formation of Children’s Christian Character in PAUD GKPI Special Congregarion. The method used in this research is a quantitative research method wit regression statistics. The population is all 13 children is PAUD GKPI Special Congregation People. Data was collected using a closed questionnaire of 30 items. The result of data analysis show that there is a positive and significant influence of parenting patterns on the formation of children’s Christian Character in PAUD GKPI Hutagalung Special Congregation: Analysis requirements test: positive relationship test obtained rxy = 0,649 rtabel =0,552 with high interpretation, thus it is know that there is a positive relationship between variables X dan Y. influence test: Regression equation test, the regression Y equation H0 is Ha obtained = 36,711+0,289 in this way optimal parenting patterns can improve the formation og Chirtian character for early childhood in PAUD GKPI Hutagalung Special Congregation.